Adopting green measures in exporting firms: What are the effects on labour market outcomes? - Nicolas Maître; Pelin Sekerler Richiard (International Labour Organization (ILO), 2024)
This study contributes to the literature on the relationship between trade, labour and environmental sustainability by providing empirical evidence at the firm level. For this purpose, it first explores whether exporting firms are more likely than non-exporting firms to adopt green measures. Second, it assesses how labour market outcomes such as productivity, wages, education level of workers, and training provided by firms may vary between green exporters and firms that do not engage in trade or undertake green measures. The study finds that exporting firms have a significantly higher probability of adopting green measures than do non-exporting firms. In addition, on average, among exporting firms, those that implement green measures tend to have higher levels of productivity, pay higher wages, offer more training and have a similar share of workers with a university degree in comparison with exporters that do not implement green measures. However, the gain in labour productivity associated with exporting and the adoption of green measures does not seem to translate into higher wages in lower-middle-income and upper-middle-income countries; it only does so in high-income countries.
Keywords: 330